Tracing the Environmental Effects of Mineral Fertilizer Application with Trace Elements and Strontium Isotope Variations - Hill, R.C.; Williams, G.D.Z.; Wang, Zhen; Hu, J.; El-Hasan, T.; Duckworth, O.W.; Schnug, E.; Bol, R.; Singh, A.; Vengosh, A. (2024)
Fertilizer utilization is critical for food security. This study examines the occurrence of trace elements (TEs) and Sr isotope (87Sr/86Sr) variations in phosphate rocks and mineral fertilizers from a sample collection representative of major phosphate producing countries. We show high concentrations of several TEs in phosphate rocks (n = 76) and their selective enrichment in phosphate fertilizers (n = 40) of specific origin. Consistent with the concentrations in parent phosphate rocks, phosphate fertilizers from the U.S. and Middle East have substantially higher concentrations of U, Cd, Cr, V, and Mo than those in fertilizers from China and India. Yet, fertilizers from China and India generally have higher concentrations of As. The 87Sr/86Sr in phosphate fertilizers directly mimic the composition of their source phosphate rocks, with distinctive higher ratios in fertilizers from China and India (0.70955-0.71939) relative to phosphate fertilizers from U.S. and Middle East (0.70748-0.70888). Potash fertilizers have less Sr and TEs and higher 87Sr/86Sr (0.72017-0.79016), causing higher 87Sr/86Sr in mixed NPK-fertilizers. Selective extraction (Mehlich III) of soils from an experimental agricultural site shows relative enrichment of potentially plant-available P, Sr, and TEs in topsoil, which is associated with Sr isotope variation toward the 87Sr/86Sr of the local utilized phosphate fertilizer.